METHODS OF CONTROL OF THE INTERNAL AUDITING STANDARDS SYSTEM IN AUDIT COMPANIES BY EXTERNAL QUALITY AUDITORS - VADIM Ovsiychuk; VALENTINA Ovsiychuk; YURY Trusov (Учёт. Анализ. Аудит)
The article describes the methods which external quality auditors could use to assess the quality of the system of internal auditing standards in audit companies. By setting the forms to execute the internal control of the system of internal auditing standards of the organization being audited, quality auditors should determine the procedures which are aimed at checking if the staff of the audit organization reviewed follow the professional requirements. The two main methods to get evidence that the employees of audit organizations are familiar with the text of internal standards are the following: review of acknowledgment sheets and questionnaires. In the process of studying the internal standards of auditing the audit team addresses the issues of completing the review check by the auditors. Quality auditors should pay special attention to the provisions which establish the principles and procedures of the review. Having summarized the methods of control of the internal auditing standards system in audit companies the authors conclude that the check of internal standards provisions by itself does not permit to make a clear judgment if the quality of work of auditors is high or low.